Sistem Pendukung Keputusan Pemilihan Bibit Sapi Unggul Madura Dengan Menggunakan Metode Analytical Hierarchy Process (AHP) Dan Simple Additive Weighting (Saw) - Putri, Dewi Amiliana; Bakir, Bakir; Hozairi, Hozairi (J-INTECH (Journal of Information and Technology), 2023)
In general, cows are mammals or herbivores which are very useful for the village community, especially the Samatan village community. In addition to the edible meat and milk that can be processed for consumption, most farmers can also use cow dung as fertilizer. Madura cattle are one of the local cattle breeds raised by community farms in Indonesia, especially on the island of Madura, East Java. Livestock is an activity that improves the economy, especially livestock. Because Many people still don't understand which type of high-quality livestock is suitable. How did it develop? In this study, researchers wanted to create a decision support system used to determine the quality of cattle. The research sample focuses on Madura cattle, superior livestock using the AHP (Analytical Hierarchy Process) SAW (Sample Additive Weighting) method and developing application decision support systems (SPK). From the calculation results of the AHP (Analytical Hierarchy Process) SAW (Sample Additive Weighting) method